Phytochemical constituents of bark essential oils of Cinnamomum zeylanicum Blume and effects on liver tissue of rats - Duaa Abd Alazem Amran,; Karim H. Al-Derawi,; Al-Saadi , Sahar (University of Thi-Qar Journal of Science, 2023)
Cinnamomum zeylanicum Blume is an evergreen tropical tree belonging to the Lauraceae family; it is a useful plant in traditional and modern medicines. Essential oils of Cinnamomum zeylanicum were prepared and identified using gas chromatography–mass spectrometry (GC-MS). For histological study 80 adult male rats were employed in this study. It is the same weight (30 ±5 gm) and 75 days in age. The animals were divided into 4 groups, with ten rats in each group.  The results indicated that C. zeylanicum bark contained 27 different phytochemical components. The main components included Cinnamaldehyde (2-Propenal, 3-phenyl-) (46.46%), 9-Methoxybicyclo, [6.1.0] nona-2,4,6-triene (31.31%), alpha-, Muurolene (7.14%) and Copaene (1.63%). Sections of livers were examined for histological abnormalities, such as the breakdown of the liver architecture and increased inflammation, in comparison to control samples, some hepatocytes were swollen with pyknotic, large nuclei and dilated sinusoids. As well as in the rats treated with noticed sever congestion of central vein (CV), degeneration and sluggish of endothelial lining larger, Bile ducts hyperplasia and necrotic hepatocytes. It can be deduced that the main component of cinnamon bark oil is cinnamaldehyde and the liver displayed some tissue changes, including hepatocyte necrosis and the existence of steatosis foci. Histological and cellular changes in liver tissue were dramatically attenuated by C. zeylanicum essential oil.